Analisis Tingkat Literasi Keuangan Syariah Pada Penyandang Disabilitas di Daerah Istimewa Yogyakarta - Johari, Sobar M; Ramadhania, Sabrina Ayu (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
This research purposes to know level of Islamic financial literacy on dibaility at Yogyakarta Region. The data is found by questionnaires method that is given to scavenger. Based on the data is found 100 respondents. The method that is used in this research is descriptive statistic analysis technique and Chi-Square analysis. There are 4 independent variable are gender, age, education, and Speanding. While, dependent variable is financial literacy in the knowledge and capability category. Based on the result test showed that scavenger in the integrated disability in Yogyakarta Region have level knowledge and capability financial literacy is in low category .Gender showed there is no difference while, age, education level, and speanding there are difference scavenger financial literacy in the disability, Yogyakarta Region.